Fire in the lake: the Vietnamese and the Americans in Vietnam. - FitzGerald, Frances, 1940- (New York, Vintage Books, 1973)
Discusses peasant society, French colonial rule, Confucianism, and the impact of modernization to show the problems of southern Vietnam.
Bibliography: p. [628]-638.
Young Adult
Young Adult
Wilson's Senior High School
Wilson's Public Library
Booklist
Keywords: Vietnam -- Politics and government; Vietnam War, 1961-1975 -- United States; Vietnam -- Politics and government; Vietnam War, 1961-1975.